The effect of alginate supplementation on the growth, feed utilization, digestive enzyme activity levels, and intestinal morphology of juvenile South African abalone (Haliotis midae) fed formulated feeds - Tlakedi, Thato (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2020)
Alginate occurs abundantly in kelp and while a few studies have quantified the effect of kelp inclusion in formulated Haliotis midae feeds, none have researched the effect of alginate inclusion on the growth of abalone fed this feed. Feeding kelp to cultured abalone affects gut structure and modulates gut bacteria, aiding digestion by upregulating enzyme activity. This farm-based experiment compared the growth, feed utilization, digestive enzyme activity levels and intestinal villi structure between abalone (1-year-old, 10 - 20 mm shell length) fed kelp-supplemented (BK) or alginate-supplemented (BA) diets and abalone fed basal (B) and fresh kelp (K) diets for a period of eight months from June 2017 to February 2018. Growth and enzyme activities were also compared between abalone that experienced dietary changes and abalone that remained on their initial diets. The tested diets were: base diet (B, 34% protein), the same base diet supplemented with fresh minced kelp (0.90% kelp [dry mass, equivalent to 0.20% alginate]; BK), base diet supplemented with sodium alginate (0.20% alginate; BA) and a fresh kelp diet (K). Alginate or kelp inclusion in a formulated feed had no significant effect on the specific growth rates (SGR), linear shell growth rates (LGR), daily percentage feeding rates (PFR), feed conversion ratio (FCR), percentage mass gain (MG) and condition factor (CF) over the eight month trial period, compared to abalone fed the base diet. In October 2017, four months since the start of the trial in June, all the groups fed formulated feeds showed significantly higher average weight gain (8.42 ± 0.72 g to 8.86 ± 0.63 g) compared to the kelp-fed group (6.68 ± 0.43 g). However, no significant differences in the average weight gain were observed between abalone fed kelp and formulated feeds at the end of this study. Furthermore, there were no significant differences in the FCR and PFR between abalone fed the base or alginate diets and abalone fed the fresh kelp diet. However, the SW diet produced significantly lower FCR (1.00 ± 0.13) and PFR (0.78 ± 0.10%) compared to the kelp diet (10.6 ± 1.40% and 8.12 ± 1.01%, respectively). All formulated diets produced non-significant LGR, MG and CF compared to the kelp diet at the end of this study. Enzyme activity levels were compared between abalone fed the test diets in July and August 2017 and February 2018. There were no significant differences in the average alginate lyase specific activity levels between abalone fed formulated diets in July and August 2017. At the end of the trial, however, the alginate diet induced significantly higher alginate lyase specific activity levels (4.89 ± 1.64 mg.mg-1 protein) compared to the base diet (1.57 ± 0.98 mg.mg-1 protein), but showed no significant differences compared to the SW (3.78 ± 0.41 mg.mg-1 protein) and fresh kelp-only diets (4.00 ± 0.62 mg.mg-1 protein). The SW diet showed no significant differences in the alginate lyase specific activity levels compared to the base diet. There were no significant differences in the chymotrypsin activity levels between the test diets throughout this study. Alginate or kelp inclusion also had no significant effect on the intestinal structure compared to the base or fresh kelp diets. This was despite a higher degree of variability in microvilli height and width being observed in abalone fed the kelp-only diet, with microvilli visibly wider and longer than in abalone fed formulated feeds. Switching abalone between some diets significantly affected the average weight gain, MG, FCR and PFR, alginate lyase, chymotrypsin and cellulase activity levels compared to abalone kept on their initial diets. The inclusion levels of kelp and alginate used in this study were likely too low to affect abalone growth as higher inclusion levels, particularly of alginate, have been found to improve fish growth. This study concluded that minced kelp and alginate inclusion in a formulated H. midae diet did not affect the SGR, FCR and intestinal morphology, but significantly affected alginate lyase and chymotrypsin activity levels. Furthermore, changes in growth and digestive enzyme activity levels coincided with dietary changes. Consequently, higher inclusion levels, particularly of sodium alginate, and the effect of dietary changes on abalone growth and digestive enzymes must be investigated in future studies.
Keywords: Abalones -- Feeding and feeds -- South Africa; Haliotis midae; Abalones -- Digestive organs; Abalones -- Morphology